PENGARUH KONTEN INSTAGRAM TERHADAP BRAND AWARENESS AEROSTREET - Asyefi, Muhammad Gestald; Widiantari, Maria Magdalena; Sejati, Veny Ari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid evolution of digital technology in the contemporary era has compelled business entities to leverage social media as a primary vehicle for marketing communications. Instagram, in particular, has emerged as a highly potent platform due to its inherently visual and interactive nature, making it exceptionally effective at capturing the attention of younger demographics. This current research was undertaken to analyze the specific influence of Instagram content, as a strategic form of promotional communication, on the brand awareness of the local footwear label, AEROSTREET. In terms of methodology, this study adopted a quantitative framework, utilizing a survey-based approach. Primary data was gathered via online questionnaires distributed to 77 active Instagram users. The subsequent data analysis involved both descriptive statistics and the Pearson correlation coefficient test to determine the relationship between variables. The empirical findings reveal that the marketing communication efforts executed through social media content have a positive and statistically significant impact on AEROSTREET’s brand awareness. This is evidenced by a correlation coefficient value of 0.699 and a significance level of 0.000. These results suggest that as the effectiveness of marketing content delivered through Instagram increases, there is a corresponding rise in consumer brand recognition. Consequently, this study serves as a valuable reference for local entrepreneurs in designing more impactful digital marketing strategies. By optimizing visual storytelling and engagement on social media, local brands can strengthen their market presence and foster deeper connections with their target audience in an increasingly competitive digital landscape.